Ruthenium nanoparticles in high-throughput studies of chemoselective carbonyl hydrogenation reactions - Gmeiner, Julia Renate; Behrens, Silke; Spliethoff, Bernd; Trapp, Oliver (ChemCatChem, 2016)
Abstract Small (≤1.4?nm) and very active Ru nanoparticles, stabilized in a polysiloxane matrix, were prepared and studied in hydrogenation reactions by the integration of catalysis and analysis. We used our strategy to combine catalytic activity and separation selectivity in a capillary microreactor, installed in a GC?MS instrument, to develop a fast and reliable screening tool for catalysis over Ru nanoparticles. A high conversion using a low catalyst loading of 0.3?mol?% and temperature and long-term stability of the catalytically active column were observed for the hydrogenation of various carbonyl compounds, which included aldehydes, ketones, and pyruvates. Additionally, we observed a high chemoselectivity for aromatic carbonyl systems. Comprehensive measurements were performed in this high-throughput experimental setup to gain important insights into the kinetics of hydrogenation reactions at the interface between heterogeneous and homogeneous catalysis.
First published: 23 December 2015
Gesehen am 19.06.2020